Androgen receptor as a mediator and biomarker of radioresistance in triple-negative breast cancer - Corey Speers (Nature Portfolio, 2017)
Radiation: Drug target found for radioresistance Drugs that block the androgen receptor (AR) protein can help make radiation-resistant breast tumors susceptible to ionizing therapy. Corey Speers from the University of Michigan, Ann Arbor, USA, and colleagues characterized the radiation sensitivity of 21 breast cancer cell lines and then paired the response data with the findings of a high-throughput drug screen to identify a medication called bicalutamide — an AR inhibitor — as one of the most potent agents for overcoming radiation resistance. The researchers then measured the expression of AR in more than 2100 human breast tumor samples and 51 breast cancer cell lines, and found that patients with triple-negative breast cancer, especially those who relapsed after radiation, had elevated levels of AR. Cell experiments with enzalutamide, a newer generation AR-blocking drug, confirmed that targeting AR helps reverse radiation resistance.